Recent advancements in multilevel inverters: topologies, modulation techniques, and emerging applications - Taha, Taha Abdulsalam; Shalaby, Mohamed; Abdul .Wahab, Noor Izzri; Zaynal, Hussein Ibzir; Hassan, Mohd Khair; Al-Sowayan, Sulaiman; Alawad, Mohamad A. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Multilevel inverters (MLIs) have become fundamental in contemporary power electronics, providing enhanced performance compared to conventional two-level inverters regarding their output voltage quality, efficiency, and scalability. This study comprehensively assesses multilevel inverter technologies, including their topologies, control systems, and various applications. The study starts with a comprehensive examination of the core concepts of MLIs, subsequently embarking on a detailed evaluation of both conventional and innovative topologies, such as diode-clamped, flying capacitor, cascaded H-bridge, and modular multilevel converters. The study further examines the control systems used in MLIs, including Pulse Width Modulation (PWM), space vector modulation (SVM), and Model Predictive Control (MPC), emphasizing their benefits and drawbacks. The applications of MLIs in renewable energy systems, electric cars, industrial drives, and grid integration are comprehensively examined. The study closes by examining growing trends, difficulties, and future research paths, emphasizing the ability of MLIs to transform power conversion systems.